Erratum: What Doesn’t Work in the European Cohesion Policy? Development Challenges of the Inner Periphery After the SARS-CoV-2 Pandemic - Editorial Team, (Quaestiones Geographicae, 2026)
ERRATUM TO: What doesn’t work in the European cohesion policy? Development challenges of the inner periphery after the SARS-CoV-2 pandemic Authors: Paweł Churski, Czesław Adamiak, Anna Dubownik, Maciej Pietrzykowski, Barbara Szyda Original Article Citation: Quaestiones Geographicae, volume 43, No 4, pp. 75-93, 2024 DOI: https://doi.org/10.14746/quageo-2024-0038 Erratum DOI: https://doi.org/10.14746/quageo-2024-0038.e Description of the Error: The legend in Figure 2 was incorrectly prepared in the publication. The description of the two types of FUAs identified as part of the grouping performed was changed. Incorrect legend description: Category 4 - First-order inner peripheries Category 5 - Second-order inner peripheries Correction: Correct legend description: Category 4 - Second-order inner peripheries Category 5 - First-order inner peripheries This correction does not affect the scientific results or conclusions. This correction affects the following elements: The applied correction clearly affects the description of the research results and enables a correct spatial interpretation of the obtained grouping results, as described in the article text. The description in the article does not require correction. The change was made to ensure the layout description aligns with its presentation on the map.